SEM Evaluation of the Hybrid Layer in Mechanical and Kinetic Prepared Cavities, Restored with Giomer - Irina Maftei; Iulia Catalina Saveanu; Oana Dragos; Ioan Danila (Romanian Society of Oral Rehabilitation, 2012)
Using restorative materials obtained by nanotechnology allows maximum penetration of the dental structures with maximum bond strength both by infiltration and adhesion. The purpose of this study was to analyze with SEM the hybrid layer in enamel and dentin, for the occlusal cavities prepared mechanically and with laser, and filled with giomer. Method The study included 10 human molars and premolars that were extracted for orthodontic or periodontal reasons, which were divided into two equal groups N = 5, each with two equal sub- groups: Group A - cavities in enamel A1 and dentin A2, prepared with laser (WaterlaseMD-Biolase) with MG6- MZ6 peaks, 30% water, 60% air with a power of 5.5 W at 20 Hz for enamel and 3W at 15 Hz for dentine; group B- enamel cavities B1 and dentin cavities B2, both high and low speed mechanical preparations with diamond cylindrical drills and no. 1 globular carbide drills. The materials used were Giomer Beautifil (Shofu), orthophosphoric acid 37%, and dental bonding agent Adper Single Bond Plus (3M ESPE). The materials were placed in a single layer and photo activated with source halogen (3M), cut lengthwise(diamond), polished, conditioned (H3PO4-35% -4s), stored(48 h), analyzed by SEM (VEGAIITESCAN and JEOLJSM 6390ª), SPSS 14.00 statistically analyzed (ANOVA, p ≤ 0.05). Results Hybrid layer analysis showed differences between groups, the average size of the SH being for Gr.A1= 5.18 mm, Gr.A2 = 15.81 mm, Gr.B1=4.24 mm, Gr.B2 = 5.83 mm. There were statistically significant differences between them at p ≤ 0.05, in favour of the samples prepared with laser and examined at the dentin. Conclusions Regardless of the group we studied, adhesion to enamel and dentin of the giomer proved optimal in terms of quality. The advantage in what HL size is concerned belonged to the LASER preparations in dentin.